AN INQUIRY OF THE PRINCIPLES OF ISLAMIC EDUCATION MANAGEMENT IN THE QUR’AN - Buto, Zulfikar Ali; Fakhrurrazi, Fakhrurrazi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This article analyzes several well-known interpretations of the principles of Islamic education management in the Qur’an, Surah al-Taubah verse 60. This analysis examines the implied meaning so that it is very relevant to current conditions regarding the principles of Islamic education management in socializing, collecting and sharing zakat to those who are entitled to receive it. This study is enriched with a particular tahlilî interpretation approach to the terminology of zakat contained in the Qur’an Surah al-Taubah verse 60. The results of the zakat distribution education management, constitutional education management principles of zakat management, education management principles for asset cleaning, ideological, doctrinal education management principles, undergraduate education management, and human resource education management.Keywords: Islamic education, management, aims giving, Qur’anic exegesis